Samoa Food and Tobacco Tax Household Survey, 2020 - World Bank (Washington, DC, 2022)
Major risk factors for NCDs in Samoa include poor nutrition, smoking, excessive alcohol consumption, and physical inactivity. Addressing all of these risk behaviors requires multisectoral, multilevel action, including efforts to change the currently unhealthy food environment. The food environment in Samoa is characterized by an excess of high fat, high salt, and calorie dense imported foods. These foods are a more affordable source of calories than fruits and vegetables, which is particularly problematic in a setting with widespread food insecurity (almost a quarter of households in Samoa experience some degree of food insecurity). Systems level approaches such as fiscal policy and legislative efforts have greater potential than individual level interventions to change the local food supply. This study aims to provide baseline data on consumption of food products subject to planned tax changes as well as to report on current tobacco and alcohol consumption. The findings are expected to serve as the basis for evaluation of the taxes to be implemented, with a post-tax survey well positioned to monitor the impact of taxes on consumer behavior, subject to the government’s planned increase of excise taxes on selected unhealthy products in the future.